P84/Zeolite-Carbon Composite Mixed Matrix Membrane for CO2/CH4 Separation - Triyanda Gunawan; Retno Puji Rahayu; Rika Wijiyanti; Wan Norharyati Wan Salleh; Nurul Widiastuti (Indonesian Journal of Chemistry, 2019)
Mixed Matrix Membranes (MMMs) which consist of 0.3 wt.% Zeolite-Carbon Composite (ZCC) dispersed in BTDA-TDI/MDI (P84 co-polyimide) have been prepared through phase inversion method by using N-methyl-2-pyrrolidone (NMP) as a solvent. Membranes were characterized by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Thermogravimetric Analysis (TGA), and Fourier Transform Infrared (FTIR). Membrane performance was measured by a single gas permeation of CO2 and CH4. The maximum permeability of CO2 and CH4, which up to 12.67 and 6.03 Barrer, respectively. P84/ZCC mixed matrix membrane also showed a great enhancement in ideal selectivity of CO2/CH4 2.10 compared to the pure P84 co-polyimide membrane.